PENGGUNAAN PATH ANALISIS UNTUK MENGUJI PENGARUH VARIABEL INTERVENING PADA PARADIGMA JALUR - Lie Liana (Jurnal Ilmiah Dinamika Teknik, 2009)
Form the variable band paradigm depict the independent variable, variable intervening and variabel dependen, variabel intervening represent the variable or mediasi. Fungtion from this variable is to mediating independent variable with the variable dependen. To test the influence of variable intervening used a method analyse the band. Analyse the band in fact usage anlyse the regresi to apraise the causality between variable which have been specified previously pursuant to basis for theory. By using determinable band analysis pattern three or more variable. that happened can represent the direct or indirect. Direcct happened if one variable influence the other variable without there variable of three which mediating mentioned variable. Indirect if three are variable of three which mediating this variable.keyword: path analysis, variable intervening, band paradigm.